Alice Ambrose and early analytic philosophy. - Connell, Sophia M. (British Journal for the History of Philosophy, 2022)
Alice Ambrose (1906–2001) is best known as Wittgenstein's student during the 1930s. Her association with probably the most famous philosopher of the twentieth century contributes to her obscurity. Ambrose is referred to in historiography of this period as 'follower' or 'disciple' but never considered in her own right as a philosopher. The neglect of her place in the history of philosophy needs to be resisted. This paper explores some of Ambrose's most interesting ideas from the early 1950s, when she developed and expanded some of Wittgenstein's inchoate suggestions and contributed to on-going debates about how to do philosophy and the role of language in the discipline. By combining an analysis of the 1950 paper "The Problem of Linguistic Inadequacy" and the 1952 paper "Linguistic Approaches to Philosophical Problems", it will be seen that Ambrose rejects the idea that ordinary language can be improved and begins to develop the view that philosophical language adapts to usage. Thus, Ambrose does not blindly follow Wittgenstein but breaks with his idea that there is something inherently wrong with the way philosophers communicate. The paper also seeks to show how marginalized philosophers become obscured in the history of the subject through the example of Ambrose.